Aegean Sponge Fishing and the Island of Kalymnos (19th-20th Centuries) - Olympitou, Evdokia, (Brill's Studies in Maritime History ;, 2024)
Before the invention of synthetic sponges, divers culled the seabeds of the Aegean for animal sponges or "sea gold" to supply global demand, while risking paralysis or death from decompression disease. This is a study of sponge diving and the impact of the industry on the inhabitants of Kalymnos and Mediterranean. It is a record of the 10,000 divers who died, the 20,000 who were paralysed between 1886 and 1910, and the women who were there to sustain them when they returned home.